Flask-like perforations on the territory of Perm Predural area in Middle Ages - Krylasova, N.B.; Podosenova, Yu.A. (Perm Federal Research Centre Journal, 2018)
Flask-like perforations belong to the number of numerous findings in the materials of the medieval archaeological monuments of Perm Ural Mountains. These artifacts were not only belt and hair ornaments in women’s medieval costume, but also performed a utilitarian function, they served as cases for needles at the end of the VII - XIII centuries. The mass character of the findings indicates that these details of the costume were spread only on the territory of Perm Ural Mountains area, their location in the monuments of neighboring archaeological cultures proves ethnocultural contacts of the medieval population of the region.